Adsorption of Lead and Cobalt from Aqueous Solution Using Unmodified Date Palm Seeds: Kinetics and Isotherms - Almhana , Nadia; Al-Saedi, Rasha; Abaas, Ishraq; Al-Tameemi, Israa M. (Journal of Engineering and Sustainable Development, 2025)
The ongoing pollution of water with heavy metals and the costly treatment methods have raised the need to search for an alternative treatment approach. In this work, a batch adsorption experiment using unmodified date palm seeds (UDPS) was conducted to investigate the effects of contact time, pH, adsorbent dose, and initial concentration on the removal rates of cobalt and lead from aqueous solution. Freundlich and Langmuir isotherms, as well as the kinetics of Pseudo-First- and second-order adsorption models, were also assessed. The results showed that equilibrium was reached at a 90-minute contact time, achieving the highest removal efficiencies of Co+2 and Pb+2 at pH 6, an adsorbent dose of 0.5 g, and initial Co+2 and Pb+2 concentrations of 10 mg/L, with maximum uptake potentials of 0.9 and 0.89 mg/g, respectively. Lead adsorption fitted slightly better to the Freundlich isotherm than to the Langmuir isotherm, whereas Co adsorption over the Langmuir isotherm. Regarding the kinetics of adsorption, the Pseudo-second order model better represented Co+2 and Pb+2 than the Pseudo-first-order model. FTIR results illustrate peaks at 3250 cm-1 and 3413 cm-1 for Co and Pb, respectively, corresponding to O=H stretching mode on the adsorbent surfaces.